Refractive and Visual Outcomes after Scleral Fixated Intraocular Lens Implantation in Children with Ectopia Lentis - Lalramhluni, Regina; Rath, Soveeta; Shrivastav, Ankita; Singh, Prem Kumar; Mayor, Rahul; Singh, Shalini; Agarwal, Manisha; Ganesh, Suma; Gurung, Chandra (Nepalese Journal of Ophthalmology, 2020)
Introduction: This study was conducted to report the refractive and visual outcome after Scleral Fixated Intraocular Lens (SFIOL) implantation in children with nontraumatic ectopia lentis. Methods: Retrospective review of the medical records of 25 eyes of 15 patients who underwent SFIOL implantation in children with non-traumatic ectopia lentis. Results: The mean best corrected visual acuity (BCVA) before SFIOL implantation was 1.07 ± 0.9 logMar units [median: 0.9, Interquartile range (ΙQR): 0.415 to 1.555] which improved to 0.41 ± 0.33 logMar units (median: 0.22, ΙQR: 0.180 to 1.555) at two months postoperative follow up. In phakic group, the mean spherical refraction preoperatively was -12.04 ± 7.82 DS (dioptre sphere) (IQR: +16 to -5.875) and postoperatively was +0.93 ± 2.67DS (IQR: -0.375 to +2). In aphakic group, the mean spherical refraction preoperatively was +12.22 ± 2.05 DS and postoperatively was +1.2 ± 1.9 DS. The mean total astigmatism preoperatively was -6.44 ± 4.95 DC (dioptre cylinder) (median: 6, IQR: -10.50 to +2) and postoperatively was -1.47 ± 0.98 DC (median: -1.5, IQR: -2 to - 0.625 ). The mean IOL induced astigmatism was -1.01 ± 0.95 DC (median -0.75, IQR: -1.33 to - 0.25). The spherical refractive equivalent was within 2 Diopter (D) of the target refraction calculated preoperatively in 20 eyes and in five eyes it was more than 2 D. Conclusion: SFIOL implantation is associated with good visual outcome with a significant improvement in the refractive error. However, a longer follow up is required to assess the change of refraction and the stability of the SFIOL.